Nectar chemistry modulates the impact of an invasive plant on native pollinators. (8th November 2015) - Tiedeken, Erin Jo; Egan, Paul A.; Stevenson, Philip C.; Wright, Geraldine A.; Brown, Mark J. F.; Power, Eileen F.; Farrell, Iain; Matthews, Sharon M.; Stout, Jane C.
Summary: Invasive species are considered a main driver of pollinator declines, yet the direct effects of invasive alien plants on pollinators are poorly understood. Abundant, invasive plant species can provide a copious nectar resource for native pollinators. However, the nectar of some plants contains secondary compounds, usually associated with defence against herbivores. The impacts of these compounds on pollinators are often unknown. We compared how consumption of grayanotoxin I and III, natural secondary compounds in the nectar of invasive Rhododendron ponticum L., affected three native bee species: a honeybee, ( Apis mellifera L.), a solitary mining bee ( Andrena carantonica, Pérez) and a bumblebee, ( Bombus terrestris, L.). Survival of the solitary bee and the bumblebee species was not affected by either grayanotoxin, but honeybees were ∼20× more likely to die when fed solutions containing grayanotoxin I. Furthermore, solitary bees were deterred from feeding and exhibited malaise behaviours indicative of sublethal toxicity in response to consumption of grayanotoxin I. In contrast, grayanotoxins did not affect bumblebee survival or behaviour, even when bees were subjected to multiple stressors (parasite infection or food stress). Our experiments suggest that while R. ponticum provides abundant floral nectar, it is only available as a food resource to pollinators that tolerate grayanotoxins. Pollinators whose health is negatively affected by grayanotoxins may experience negative impacts from R. ponticum invasion directly (if they consume R. ponticum nectar) or indirectly (if native floral resources are replaced by R. ponticum ). Our study makes a novel comparison of the effects of a natural nectar secondary compound on three pollinator species and clearly demonstrates drastic variation in the responses of different key pollinator taxa to a nectar toxin. Our findings are thus in congruence with literature demonstrating the varying effects of invasive plant chemistry on native foliar herbivores, and our work demonstrates that nectar chemistry should be taken into account when determining the impacts of plant invasion for native pollinators. Abstract : Lay Summary